Ko measurements on Bangkok clay - Supachai Tantikom; Balasubramaniam, A.S.; Ohta, Hideki; Prinya Nutalaya; The Government of New Zealand (Bangkok : Asian Institute of Technology, 1982)
There are various methods in determining Ko which could be done both in the laboratory and in the field, however, there is an argument that which method gives the best estimation of Ko. A series of laboratory tests by Preconsolidation Pressure Simulating Method, Consolidation under a Constant Stress Ratio Method, Consolidation under Zero Lateral Strain Condition and Field Hydraulic Fracturing Test were carried out to determine the K0 values of Bangkok Clay at AIT campus. The results showed that the laboratory methods give somewhat likely values of Ko while fracturing method gives lower values.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering, School of Engineering and Technology
Thesis (M. Eng.) - Asian Institute of Technology, 1982
Keywords: Clay -- Thailand -- Bangkok -- Testing